High Speed Nyquist Analog To Digital Converter In CMOS - Seemi, Shazia (2006)
High speed requirements of ADCs (Analog to Digital Converter) in the fields of data storage and digital communication has led to finding new ways to accomplish high speed without sacrificing dynamic and static performance.